Improvement of physical culture among children and youth in extracurricular education institutions - Natalia Tikhonova; Anastasiya Bondar (Kharkiv State Academy of Physical Culture, 2014)
Purpose: is to improve the physical culture extracurricular education institutions. Materials and Methods: the study employed a range of scientific methods, including literary sources and documents analysis; expert evaluation method; methods of system analysis; sociological methods; statistical methods, pedagogical experiment. The study involved 20 managers, 120 coaches from sport organizations, as well as 4 managers of physical culture and sports administration, 20 top-scientists experts in the problem under study. Results: the "complex of arrangements that are supposed to involve children and yourth to extracurricular education institutions " was developed the main problem during the pedagogical experiments. Conclusions: the complex introduction and the decision of its main objectives was to increase financial profit by 33% (UK «Ayumi»), the number of involved students increas by 24% in the UK «Ayumi» and by 2.2% for the initial training of "SC Youth School in Aquatics von Yana Klochkova." The effectiveness of implementing measures confirm the results of expert evaluation scholars and practicians in the physical culture and sport spher. Experts from both groups appreciated the level of expected efficiency (4.6 and 5.0 points out of 5 points).